2018
DOI: 10.1111/resp.13360
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐dependent and independent airway remodelling in asthma

Abstract: These findings suggest that inner and outer wall thickening coexists with inflammation, whereas thickening of the ASM layer and basement membrane may be present even in the absence of inflammation. Remodelling of the ASM layer and basement membrane may therefore be less susceptible to anti-inflammatory therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…The ASM is at the core of asthma symptoms and its thickening results from the perpetual stimulation with numerous anabolic stimuli including growth factors, spasmogens, and immune modulators (30,31). The persistent reduction of ASM thickening associated with the long-term benefits of bronchial thermoplasty indicates that punctual interventions directed against the ASM bear therapeutic potential (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…The ASM is at the core of asthma symptoms and its thickening results from the perpetual stimulation with numerous anabolic stimuli including growth factors, spasmogens, and immune modulators (30,31). The persistent reduction of ASM thickening associated with the long-term benefits of bronchial thermoplasty indicates that punctual interventions directed against the ASM bear therapeutic potential (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…ASMCs phenotype is linked with the activation of the deposition of extracellular matrix proteins and pro-remodeling function of recruited fibrocytes (Mattoli, 2015;Boulet, 2018), exacerbating airway remodeling. It was found that ASMCs proliferation was aggravated in asthmatic patients and there were more ASMCs from asthma subjects than from healthy subjects in post-mortem airway sections (Fujita et al, 2011;Elliot et al, 2018;James et al, 2018). In vivo, ASMCs thickening and proliferation were verified to be promoted in house dust mite-induced murine (Yang et al, 2017).…”
Section: Lncrnas Associated With Asmcs Proliferation In Asthma Pathogmentioning
confidence: 94%
“…However, there is no clear hypothesis regarding by which mechanism(s) the microorganisms and non-biological factors, such as dust, lead to the same clinical symptoms that are diagnosed as asthma. Nevertheless, the hypothesis is supported by the observation that airway wall remodeling often occurs prior to the detection of any inflammation [16,23]. In children with severe asthma, airway wall remodeling correlated with eosinophilia, but not with type-2 cytokines [24].…”
Section: Asthmamentioning
confidence: 99%